2010
DOI: 10.1111/j.1471-4159.2010.06608.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial reduction of BACE1 improves synaptic plasticity, recent and remote memories in Alzheimer’s disease transgenic mice

Abstract: J. Neurochem. (2010) 10.1111/j.1471‐4159.2010.06608.x Abstract β‐Site amyloid precursor protein cleaving enzyme 1 (BACE1) initiates amyloid‐β (Aβ) generation that is central to the pathophysiology of Alzheimer’s disease (AD). Therefore, lowering Aβ levels by BACE1 manipulations represents a key therapeutic strategy, but it remains unclear whether partial inhibition of BACE1, as expected for AD treatments, can improve memory deficits. In this study, we used heterozygous BACE1 gene knockout (BACE1+/−) mice to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 70 publications
7
109
0
Order By: Relevance
“…It is also well documented that genetic reductions of BDNF or TrkB deteriorate basal synaptic transmission and/ or LTP at the hippocampal Schaffer collateral-CA1 pathway and cause memory deficits in mice (Korte et al, 1995;Linnarsson et al, 1997;Minichiello, 2009;Minichiello et al, 1999;Pang and Lu, 2004;Patterson et al, 1996). Consistent with these results, we recently reported that partial reductions of Ab induced by heterozygous BACE1 gene deletion (BACE1 + /-) rescue synaptic and mnemonic dysfunctions in 5XFAD mice with the restoration of reduced hippocampal BDNF and TrkB phosphorylation to normal levels (Kimura et al, 2010). Taken collectively, our results indicate that BDNF-TrkB dysfunction is a crucial mechanism downstream to Ab accumulation in 5XFAD mice, and that reversal of the deficient BDNF-TrkB signaling with 7,8-DHF may be sufficient to directly ameliorate memory impairments associated with AD.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It is also well documented that genetic reductions of BDNF or TrkB deteriorate basal synaptic transmission and/ or LTP at the hippocampal Schaffer collateral-CA1 pathway and cause memory deficits in mice (Korte et al, 1995;Linnarsson et al, 1997;Minichiello, 2009;Minichiello et al, 1999;Pang and Lu, 2004;Patterson et al, 1996). Consistent with these results, we recently reported that partial reductions of Ab induced by heterozygous BACE1 gene deletion (BACE1 + /-) rescue synaptic and mnemonic dysfunctions in 5XFAD mice with the restoration of reduced hippocampal BDNF and TrkB phosphorylation to normal levels (Kimura et al, 2010). Taken collectively, our results indicate that BDNF-TrkB dysfunction is a crucial mechanism downstream to Ab accumulation in 5XFAD mice, and that reversal of the deficient BDNF-TrkB signaling with 7,8-DHF may be sufficient to directly ameliorate memory impairments associated with AD.…”
Section: Discussionsupporting
confidence: 76%
“…Spontaneous alternation performance was tested using a symmetrical Y-maze, as described previously (Kimura et al, 2010;Ohno et al, 2004). Each mouse was placed in the center of the Y-maze and was allowed to explore freely through the maze during an 8-min session.…”
Section: Spontaneous Alternation Y-maze Testmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested the effects of TMAO on spatial working memory in mice with the Y‐maze (Kimura, Devi & Ohno, 2010; Ohno et al., 2004) (Figure 2a–d). There was no significant difference among the four groups in the total number of arms entered, which indicated the mice in the four groups had similar working memories (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that BACE1 inhibitor ameliorated the memory defects resulting from changes in the quantity and distribution of neurotoxic βCTF (Kimura et al, 2010). In-depth understanding of the involvement of βCTF in neurodegeneration is an important determinant for the use of BACE1 inhibitor and γ-secretase inhibition as major therapeutic strategies for AD; however, there is controversy about which one would be more appropriate (Golde and Younkin, 2001).…”
Section: Discussionmentioning
confidence: 94%